Emergence of antigenic variants of Foot-and-Mouth Disease Virus serotype O in Ecuador and preliminary evaluation of a field strain as a vaccine candidate - Maradei, Eduardo (2014)
Foot-and-Mouth Disease Virus serotype O has been circulating regularly throughout most provinces of Ecuador, one of the two South American countries that still remain endemic, although satisfactory vaccination coverage was reported. This study concentrates in the characterization of isolates collected during 2008–2011, focusing particularly on the antigenic and immunogenic relationships of the field viruses with the O1/Campos vaccine strain in use in the region and with an experimental vaccine formulated with a representative strain of the 2010 epidemic. The results established that antigenically divergent variants poorly protected by the vaccine in use emerged and co-circulated in a limited period of time. A monovalent vaccine formulated with the representative 2010 strain elicited high antibody titers and protected against challenge with homologous virus. In addition, cross-reactive antibodies to predominant viruses in the region were established. In overall this study indicates the ability of the virus to diversify under field conditions in which a vaccine strain with poor match is applied, and the potential of the selected 2010 field virus as a vaccine candidate for incorporation into strategic antigen banks and/or for addition to current formulations for systematic vaccination, in order to prevent the emergence of even more divergent isolates in the future.